Response pattern of hemocyanin to Vibrio parahaemolyticus infection and its immune function in the swimming crab Portunus trituberculatus - Dongfang Sun; Yukun Li; Jianjian Lv; Junyang Guo; Ping Liu; Baoquan Gao (Aquaculture Reports, 2023)
Hemocyanin is a critical oxygen-transporting protein exhibiting multiple physiological functions, including protein storage and transportation, osmolarity regulation, molting, and immunomodulation in arthropods and mollusks. However, the immune function of hemocyanin in Portunus trituberculatus is rarely reported. Here, we identified ten subunit genes within the hemocyanin family from the P. trituberculatus genome. These genes exhibited conserved functional domains and copper ion binding sites. Building upon prior research, we specifically focused on investigating the immune functions of PtHc1 and PtHc2. Tissue expression analysis revealed that PtHc1 and PtHc2 were prominently expressed in the hepatopancreas and hemocytes. Upon infection with Vibrio parahaemolyticus, both PtHc1 and PtHc2 demonstrated a similar expression pattern, characterized by a gradual upregulation of expression levels in the hepatopancreas. While within the hemocytes, they exhibited a trend of initial downregulation followed by subsequent upregulation in expression. In addition, Recombinant hemocyanin was able to inhibit bacterial proliferation in a dose-dependent manner, with inhibition rates of 40 % and 39 % when the recombinant proteins of PtHc1 and PtHc2 reached 0.03 mg/mL, respectively. Besides, V. parahaemolyticus challenge resulted in a significant 20–23 % increase in mortality in P. trituberculatus following knockdown of PtHc1 and PtHc2. Overall, our study sheds light on the immune-related functions of PtHc1 and PtHc2 in P. trituberculatus, revealing their potential as key players in defending against pathogenic threats like V. parahaemolyticus. These results enriched the field of innate immunity in crustacean and providing a theoretical basis for disease resistance breeding.